Effectiveness Of Tele-Counseling In Enhancing Self-Care And Metabolic Markers In Type 2 Diabetes Patients Among The Coastal Areas: A Quasi-Experimental Study - Saltar, Laode; Said, Muhammad Sulkifly; Bayu, Wisnu Catur (Jurnal Kesehatan Manarang, 2025)
Tele-counseling has gained prominence as an effective tool for managing chronic diseases, including type 2 diabetes, particularly in underserved regions. This study aimed to assess the effectiveness of tele-counseling in improving self-care behaviors and metabolic markers in type 2 diabetes patients residing in the coastal areas of Kendari City, Southeast Sulawesi, Indonesia. A quasi-experimental design was employed, involving 70 participants who were randomly assigned to two groups: an intervention group (n = 35), which received tele-counseling for six weeks, and a control group (n = 35), which continued standard care. The primary outcomes measured included self-care behavior, fasting blood glucose (FBG), low-density lipoprotein (LDL) cholesterol, body weight, and blood pressure, all assessed at baseline and again six weeks after the intervention. Statistical analyses, including paired t-tests, Wilcoxon tests for non-normally distributed data, and independent t-tests for between-group comparisons, were conducted. Results indicated that the intervention group experienced significant improvements in self-care behavior (p < 0.001), along with reductions in FBG (p < 0.001), LDL cholesterol (p < 0.001), systolic blood pressure (p = 0.001), diastolic blood pressure (p = 0.003), and body weight (p < 0.001). In contrast, the control group showed minimal changes. These findings suggest that tele-counseling is an effective intervention for enhancing self-care behaviors and improving key metabolic markers in type 2 diabetes patients, particularly in coastal areas with limited access to healthcare services. This study provides valuable insights into the application of telemedicine for chronic disease management in underserved regions. Further research is recommended to examine the long-term effects of tele-counseling on diabetes management and to explore its scalability in other remote and rural areas.